SEM Evaluation of Thermal Effects Produced by a 445 nm Laser on Implant Surfaces - Daniele Pergolini; Gaspare Palaia; Riccardo De Angelis; Federica Rocchetti; Gian Marco Podda; Gianluca Tenore; Alessandro Del Vecchio; Michela Relucenti; Umberto Romeo (MDPI AG, 2023)
The aim of this in vitro study was to evaluate thermal effects on implant surfaces using a 445 nm diode laser (Eltech K-Laser Srl, Treviso, Italy) with different power settings and irradiation modalities. Fifteen new implants (Straumann, Basel, Switzerland) were irradiated to evaluate surface alteration. Each implant was divided into two zones: the anterior and posterior areas. The anterior coronal areas were irradiated with a distance of 1 mm between the optical fiber and the implant; the anterior apical ones were irradiated with the fiber in contact with the implant. Instead, the posterior surfaces of all of the implants were not irradiated and used as control surfaces. The protocol comprised two cycles of laser irradiation, lasting 30 s each, with a one-minute pause between them. Different power settings were tested: a 0.5 W pulsed beam (T-on 25 ms; T-off 25 ms), a 2 W continuous beam and a 3 W continuous beam. Lastly, through a scanning electron microscopy (SEM) analysis, dental implants' surfaces were evaluated to investigate surface alterations. No surface alterations were detected using a 0.5 W laser beam with a pulsed mode at a distance of 1 mm. Using powers of irradiation of 2 W and 3 W with a continuous mode at 1 mm from the implant caused damage on the titanium surfaces. After the irradiation protocol was changed to using the fiber in contact with the implant, the surface alterations increased highly compared to the non-contact irradiation modality. The SEM results suggest that a power of irradiation of 0.5 W with a pulsed laser light emission mode, using an inactivated optical fiber placed 1 mm away from the implant, could be used in the treatment of peri-implantitis, since no implant surface alterations were detected.